Pengaruh Pelatihan Dan Pengalaman Kerja Terhadap Kinerja Pegawai Pada Sekolah Polisi Negara Polda Metro Jaya - Ramdani Haryadi Irzan; Endang Silaningsih; Tini Kartini (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This study aims to identify the effects of simultaneous and partial training and work experience on employee performance, as well as to determine the most dominant effect between training and work experience on employee performance. The research method used is the quantitative method. The population in this study is employees in the neighborhood of the Polda Metro Jaya State Police School as many as 235 employees. The sampling of 100 employees was done by simple random sampling. The data analysis method uses multiple linear regression with the help of SPSS 20.0 software. Research results show that simultaneous and partial job training and experience have an effect on employee performance, as well as a dominant variable in influencing employee performance, namely job experience.